The Self-Regulated Learning: Social Cognitive Theory - Saragih, Fernando (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Self-regulated learning is one illustration of the development of students' character, where this character is absolute for students. Based on this, researchers are interested in the condition of learning independence and the factors that influence it (peers, learning motivation, and self-efficacy). The approach used in this research is quantitative. The data collection method used is the explanatory research method (questionnaire). The questionnaire consists of 47 statements and each statement has 4 choices. All statements in the questionnaire are valid and reliable to test (CFA). This research used a simple random sampling technique with SMM analysis with 120 respondents. The results show that peers directly have a positive effect (0.0723) on learning independence, but it is not significant (0.3965> 0.05). Different things can be seen in the indirect influence, namely on learning motivation, self-efficacy which shows a positive influence (m1 of 0.0971, m2 of 0.1783, m1 and m2 of 0.2444) and significance (BootLLCI and BootULCI > 0).